The design of everyday things - Norman, Donald A. (Tantor Media, Inc., 2011)
First, businesses discovered quality as a key competitive edge; next came science. Now, Donald A. Norman, former Director of the Institute for Cognitive Science at the University of California, reveals how smart design is the new frontier. The Design of Everyday Things is a powerful primer on how-and why-some products satisfy customers while others only frustrate them.
Keywords: Industrial design -- Psychological aspects; Human engineering; Business; Ergonomics; Technology; Nonfiction; Design & UI; Design; Aspect psychologique; Ergonomie; Affaires; ergonomics; Industrial design; Psychological aspects; Downloadable audio books; Audiobooks; Livres audio